DESIGN ANALYSIS OF AXIAL FLUX PERMANENT MAGNET GENERATOR FOR EXHAUST AC VERSION-3 TYPE B OUTPUT WIND POWER PLANT PROTOTYPE - Alam, Muhammad Ramadhan Noor; Golwa, Gian Villany (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Outside AC exhaust wind power plant is one of the micro-scale renewable energies developed in the last five years. One of the main components of a power plant is a generator. The generator is a device that converts mechanical energy into electrical energy. An axial flux permanent magnet generator is believed to be the most appropriate generator for a power plant with a low-speed wind power source, such as outside AC exhaust. A design analysis needs to be done to produce an axial flux permanent magnet generator capable of producing 12vdc electric voltage, which will be used to charge the battery. This research uses the theoretical calculation analysis method on three rotor designs with different sizes and obtained rotor design 1 with the most considerable maximum flux value of 0.000998352 Wb. The calculation of the generator output planning signifies that to obtain an output voltage of 12 Vdc at a frequency of 20 Hz, 166 turns of wire are needed. The output of 12.8 Vdc was successfully generated after the generators were connected in series parallel at a frequency of 27.5 Hz. The wind speed entering the power plant inlet was 5.8 m/s, with generator one at a speed of 682 rpm, generator two at 749 rpm, and generator three at 888 rpm, which will then be used to charge the 12 Vdc battery. After a load test using a 12 Vdc 6Watt lamp on the designed axial flux permanent magnet generator, it can be seen that the voltage drop begins to occur at a frequency of 22.5 Hz when the current flow begins to rise. During the no-load test, at a frequency of 22.5 Hz, the measured DC voltage was 9.2 Vdc. Meanwhile, when testing with a 12 Vdc 6Watt lamp load at a frequency of 22.5 Hz, the measured voltage is 5 Vdc. There is a voltage drop of 4.2 Vdc. Furthermore, there is a voltage drop of 2.8 Vdc, 3.8 Vdc, 4.6 Vdc, and 5.2 Vdc at 25 Hz, 27.5 Hz, 30 Hz, and 32.5 Hz. This prototype of an outside AC exhaust wind power plant is expected to be useful for daily needs in the community.